Syariah Regional Regulations in Aceh and Banjar: An Aspect of Religious Freedom - Ahmad, Rusniah; Fikri, Zainal; Halim, Rohizan (Akademia Baru, 2017)
This article examines the nature of regional regulations on Friday prayer in Aceh and Banjar, South Kalimantan. It argues that the nature of such bylaws cannot be explained solely in terms of Islamic law because there are other norms which served as the bases. They are secular ideological values of respect and freedom. Following Menski’s kite model of law as a methodological tool, this study analysed the hybrid combination of those norms